Evaluasi User Experience Menggunakan Metode Usability Testing dan User Experience Questionnaire (UEQ) (Studi Kasus: Website Superprof.co.id dan Zonaprivat.com) - Tasya Junita Maulani; Suprapto Suprapto; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The more rapid advances in technology encourage people to fulfill their needs and wishes through the internet. In education, one of benefit is that it can make easier for system users to search for various information about education, such as searching for online teachers. One of the websites that can provide services to find quality or online tutors is Superprof.co.id and Zonaprivat.com. Both websites are in the same sector and have functionality and competitors in the same industry. This research aims to get feedback from each user, take measurements and compare the User Experience from the two websites. This research uses Usability Testing and User Experience Questionnaire (UEQ) methods. Usability testing or scenario testing will be fulfill on 10 respondents based on 4 parameters, namely task completed, time per completed task, error rate, and number of clicks. The User Experience Questionnaire (UEQ) test were distributed to 25 respondents and has 6 measurement scales, including attractiveness, perpicuity, efficiency, dependability, simulation, and novelty. After do testing and filling in the questionnaire, responses and problems encountered by respondents will be obtained when conducting scenario testing. From the tests that have been done, it can be deduce that the Superprof.co.id website gets better test scores than the Zonaprivat.com website.